Th1 and Th2 immune responses related to pelvic endometriosis - Podgaec,Sergio (2010)
OBJECTIVE: This study analyzed the relationship between clinical characteristics of endometriosis and Th1/Th2 immune response patterns. METHODS: A prospective study was performed with 65 patients with endometriosis (Group A) and 33 without the disease (Group B). Measurement of IL 2, 4 and 10, TNF-alpha and IFN-gamma was carried out in peripheral blood and peritoneal fluid. RESULTS: Serum TNF-alpha was higher in patients with endometriosis who had deep dyspareunia compared to controls (mean 4.5 pg/ml and 2.3 pg/ml, p<0.05). Among these patients (n=32), 65.5% had deep endometriosis. Patients with endometriosis and infertility had higher IL-2 concentrations in peritoneal fluid than controls (mean 5.9 pg/ml and 0.2 pg/ml, p<0.05). Among these patients (n=22), 63.5% (n=14) had deep endometriosis. A higher concentration of IL-10 was also observed in patients with ovarian endometriosis when compared to those without this type of disease, as well as when compared to control group patients (mean 50pg/ml, 18.7pg/ml and 25.7pg/ml, p<0.05). CONCLUSIONS: These results suggest that when specific clinical data are associated with a higher production of certain cytokines, there is a Th1 response pattern that may be related to deep infiltrating endometriosis.